2002
DOI: 10.1902/jop.2002.73.11.1253
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Markers for Prediction and Assessment of Treatment Outcome Following Non‐Surgical Periodontal Therapy

Abstract: These results suggest that the combination of P. gingivalis and B. forsythus, as well as the level of P. gingivalis, is useful in assessing treatment outcome. Furthermore, the high level of A. actinomycetemcomitans before SRP is a possible valuable predictor of treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 15 publications
3
43
1
1
Order By: Relevance
“…In our study, although no significant difference in detection frequencies was found, SRP significantly reduced the counts of the periodontal pathogens Fn, Pg, and Pi, but not Aa, which is consistent with the work of others (Doungudomdacha et al, 2001;Pawlowski et al, 2005). Moreover, the fact that no difference in the amount of Aa was found after SRP in our study is also consistent with a study by Fujise et al (2002), which found that SRP did not significantly change the level of Aa using the qRT-PCR technique. The observed difference in bacterial loads but not presence after periodontal treatment in this study supports the idea that the levels of bacterial species, rather than their presence, are important in evaluating periodontal therapeutic effects .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, although no significant difference in detection frequencies was found, SRP significantly reduced the counts of the periodontal pathogens Fn, Pg, and Pi, but not Aa, which is consistent with the work of others (Doungudomdacha et al, 2001;Pawlowski et al, 2005). Moreover, the fact that no difference in the amount of Aa was found after SRP in our study is also consistent with a study by Fujise et al (2002), which found that SRP did not significantly change the level of Aa using the qRT-PCR technique. The observed difference in bacterial loads but not presence after periodontal treatment in this study supports the idea that the levels of bacterial species, rather than their presence, are important in evaluating periodontal therapeutic effects .…”
Section: Discussionsupporting
confidence: 93%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Another 11 reported a differential response to treatment depending on the detection or lack of detection of specific microorganisms. [23][24][25][26][27][28][29][30][31][32][33] The remaining papers were included primarily as background references. [1][2][3][4][5][6][7][8][9][34][35][36][37][38][39][40][41] On preliminary inspection of the publications that were considered relevant to this review, it became obvious that the papers were quite heterogeneous with respect to their objectives, methods of investigation, data collected, and availability of controls, if any.…”
Section: Resultsmentioning
confidence: 99%
“…Numbers of P. gingivalis, T. forsythia and T. denticola in subgingival biofilms are increased in sites with higher PPD and BOP (Mineoka et al, 2008). High levels of P. gingivalis are more frequent in sites with less reduction of PPD or with the presence of BOP, following scaling and root planing (Fujise et al, 2002). In a previous study, we showed that a significant positive correlation existed between the detection of P. gingivalis by RT-PCR and the periodontal parameters such as PPD and CAL (Tomita et al, 2013).…”
Section: Discussionmentioning
confidence: 99%